A Study on Nutraceuticals - Manya Bajaj (International Journal of Nutrition, 2024)
Hippocrates trusted foodstuff, maybe medicine, and healthcare management, administration, and costing are important. Nutraceuticals, derived from
Keywords: nutraceuticals